The reality of applying the alternative Evaluation in the first cycle schools in the city of Hama from the point of view of the educational supervisors (Journal of Hama University, 2026)
The current research aimed to identify the reality of the implementation of alternative assessment in primary schools in Hama from the perspective of supervisors. Differences in this reality were identified according to variables (academic qualification, number of years of experience, and training courses). The primary sample consisted of (33) male and female supervisors. A questionnaire consisting of (35) items distributed across six axes was used. The results showed:- The reality of the implementation of alternative assessment in primary schools in Hama, from the supervisors' perspective, was high.- There were statistically significant differences between the average scores of sample members on the strategic dimensions (performance-based assessment, self-assessment, and observation-based performance assessment) according to the educational qualification variable, in favor of those with higher educational qualifications.- There were statistically significant differences between the average scores of sample members on the questionnaire as a whole and on all its dimensions, except for the dimension (self-assessment strategy), according to the variable number of years of experience, in favor of those with more years of experience (10 years or more). There are statistically significant differences between the average scores of sample members on the strategic dimensions (performance-based evaluation, self-evaluation, observation-based performance evaluation) (performance evaluation by written tests) according to the training courses variable, in favor of 3 courses or more.Keywords: alternative calendar, first episode, mentors.
Keywords: alternative evaluation; first episode; mentors